PENERAPAN UI/UX PADA SITUS TOKO KUE BUNDA AL MENGGUNAKAN METODE DESIGN THINKING - Edward, MA Algifari; Setiawan, Iwan Rizal; Asriyanik, Asriyanik (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
Abstract. Information and communication technology has developed very rapidly in various fields such as marketing and buying and selling. Technology that is often used by all groups, namely the internet, one of the uses of the internet is to search for information. According to a survey by the Association of Indonesian Internet Service Providers (APJII), around 78.19% or 215.6 million of Indonesia’s population already use the Internet and use it for product marketing and buying and selling transactions. In the culinary industry, the use of Internet technology has a significant influence. Reports from Google and Temasek in 2023 show rapid growth in the e-commerce sector in Indonesia. The value of e-commerce transactions is predicted to reach 1,346 trillion rupiahs. In internet media as a means of marketing a product, not all culinary shops can take advantage of this, because of that a solution was made for creating a website that pays attention to users with the design thinking method. Making this cake shop website includes marketing products and providing information related to Bunda AL Cake Shop, the results of this research have been carried out on several respondents who have online shopping experience and several customers of Bunda AL Cake Shop. As a result of the respondents’ experience in using the Bunda AL Cake Shop website, 7 out of 8 respondents liked the website appearance design and it was very easy to understand the information provided on the website.